The Success Of Porkes Learning Through The Application Of Learning Media In Class IV SD Negeri 003 Kepenuhan - Lasri Suhaimi L (STKIP Rokania Pasir Pangaraian, 2022)
The subject of Physical Education, Sport and Health (PJOK) is a very important subject for students to study, because with knowledge of health and sports training, students can strengthen their bodies, one of which is to increase endurance (immunity). Media plays an important role in learning every lesson, including in the PJOK map. The creativity of educators is very important for the success of learning. Media modifications that are adapted to local wisdom will have a positive impact on student learning outcomes. The purpose of this paper is to describe the importance of media to PJOK learning outcomes in schools. This article is equipped with an analysis using the review method of references published online related to learning media. The positive impact on learning outcomes was also analyzed. The results of the analysis show that research on the importance of learning media has a significant effect on PJOK learning outcomes. The development of PJOK media has been widely carried out in various sports. With the development of information technology, the development of PJOK learning media is mostly done using interactive media. The creativity of educators who use the concept of local wisdom when modifying media also greatly influences PJOK learning outcomes